Three-Dimensional Cell Cultures as a Research Platform in Lung Diseases and COVID-19 - da Silva da Costa, Felipe Allan [UNESP]; Soares, Murilo Racy; Malagutti-Ferreira, Maria José [UNESP]; da Silva, Gustavo Ratti; Lívero, Francislaine Aparecida dos Reis; Ribeiro-Paes, João Tadeu [UNESP] (Springer Nature, 2021)
Background
Keywords: Chronic respiratory diseases; Lung-on-a-chip; Organoid; SARS-CoV-2; Spheroid